MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA DENGAN PENDEKATAN BRAIN BASED LEARNING - Helmahria Helmahria; Abdul Hamid; Sunarti Sunarti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2017)
Abstract. The aims of this research to determine the activities of teachers, activites of students, science process skills, cognitive, affective, and students response. The design research was used classroom action research with 2 cycles. Each cycle consists of planning, action, observation and reflection. The first and second cycle consisted of two meetings. The subjects were 29 students of XI IPA 3 SMAN 4 Banjarmasin. Research instruments in form of test and non-test. The results data showed that Brain Based Learning (BBL) approach can improved activity of the teachers at 5 in good categories, activity of students at 9,75 in good categories, science process skills from good enough to good categories, cognitive results increasing from a score of 60,06 to 87,06, affective students aspect from good enough in the first cycle to good in the second cycle, students class responded positively to learning by using Brain-Based Learning (BBL) approach.Keywords: brain-based learning, science process skills